2003
DOI: 10.1161/01.atv.0000046231.17365.9d
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interplay Between Angiotensin II and Nitric Oxide

Abstract: Abstract-Angiotensin II (Ang II) and nitric oxide (NO) signaling pathways mutually regulate each other by multiple mechanisms. Ang II regulates the expression of NO synthase and NO production, whereas NO downregulates the Ang II type I (AT1) receptor. A ngiotensin II (Ang II), the primary effector of the renin-angiotensin system (RAS), is a multifunctional hormone that plays an important role in vascular function. The local RAS, acting in both autocrine and paracrine fashions, is also functionally operative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
160
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 213 publications
(171 reference statements)
4
160
1
4
Order By: Relevance
“…37 In cultured endothelial cells, Ang II may increase the release of ET-1. 38 In the present study, significant increased systemic venous levels of ACE activities were found in psychogenic and organogenic ED subgroups compared to controls.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…37 In cultured endothelial cells, Ang II may increase the release of ET-1. 38 In the present study, significant increased systemic venous levels of ACE activities were found in psychogenic and organogenic ED subgroups compared to controls.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Almentioning
confidence: 99%
“…Many vascular diseases are associated with imbalance of Ang II and NO actions. 37 Park et al 39 reported that the deletion of polymorphism in the ACE gene, the DD genotype, as a marker of general vascular disease, may be seen more frequently in men with a diagnosis of vasculogenic erectile dysfunction. It has been suggested that ACE inhibitors might be used in the treatment of vasculogenic ED.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Almentioning
confidence: 99%
“…15 We and others have shown the beneficial effects of this compound not only on hemodynamics, but also on cardiovascular remodeling. [15][16][17][18] As sGC/cGMP activation has been shown to interfere with RAS, 19,20 we tested the hypothesis that the direct stimulation of sGC with BAY 41-2272 could attenuate myocardial fibrosis by inhibiting RAS activation. In this study, we used rats with pressure overload induced by suprarenal aortic constriction (AC), a model of hypertensive heart disease accompanied by fibroblast and RAS activation.…”
Section: Introductionmentioning
confidence: 99%
“…NO and Angiotensin II (AII) antagonize each other in many vascular functions, such as cell growth, apoptosis, and inflammation. AII has a central role in the generation of oxidative stress in the vessel wall (2).…”
Section: Introductionmentioning
confidence: 99%